The Impact of AUKUS on Strategic Stability in the Asia Pacific - Arooj Fatima Kazmi (CISS Insight Journal, 2023)
AUKUS, the trilateral partnership that the United States and United Kingdom have created with Australia, affects regional strategic stability and rebreaks the spirit of a taboo that forbids nuclear weapon states from transferring nuclear weapons and related technologies to states either party or non-party to the Treaty on Non-Proliferation of Nuclear Weapons. The NPT-based nuclear non-proliferation regime is rooted in the aspiration of improving global security, reducing the risk of nuclear war, building strategic stabili-ty, and ultimately disarmament of all nuclear-armed states. The transfer of nuclear-powered attack submarines and disruptive technologies to Australia is clearly bound to increase strategic instability and foment further nuclear proliferation. AUKUS will also fuel great power rivalry in and outside the Asia Pacific and Indian Ocean Region. This paper examines the implications of AUKUS in the Asia Pacific region, particularly, strategic stability, and the non-proliferation regime. A qualitative case study approach is adopt-ed. Data has been derived from official documents, journal articles, books, and newspaper articles and analyzed through the balance of power paradigm.